Digital Transformation of SMEs Financial Behavior in the New Normal Era - Wiyono, Gendro; Kirana, Kusuma Chandra (University of Merdeka Malang, 2021)
This study aims to determine whether there has been a digital transformation of financial behavior in the use of fintech by micro, small and medium enterprises (SMEs) in Indonesia with the Covid-19 Pandemic. The study used a population of SMEs in all provinces, while the sample collected was 84 SMEs from 19 provinces in Indonesia. Data analysis using variance-based SEM with SmartPLS 3.2.9 software tools. The results show that the Covid-19 pandemic has an effect on SMEs (old behavioral intention) in using fintech, and this is a strengthening of the influence on new behavior in using fintech (new behavioral intention). Meanwhile, the New Normal policy also has a positive and significant effect on the current behavior of using fintech (new behavioral intention). As for the new normal as a moderating variable, old behavioral intention to new behavioral intention has no significant role, this is because before the new normal, many SMEs used fintech. Suggestions for SMEs to continue to take advantage of fintech in carrying out their business activities to avoid the impact of Covid-19 and the smooth running of their business.DOI: https://doi.org/10.26905/jkdp.v25i1.4954